2023
DOI: 10.1364/aop.484298
|View full text |Cite
|
Sign up to set email alerts
|

Controlling light propagation in multimode fibers for imaging, spectroscopy, and beyond

Abstract: Light transport in a highly multimode fiber exhibits complex behavior in space, time, frequency and polarization, especially in the presence of mode coupling. The newly developed techniques of spatial wavefront shaping turn out to be highly suitable to harness such enormous complexity: a spatial light modulator enables precise characterization of field propagation through a multimode fiber, and by adjusting the incident wavefront it can accurately tailor the transmitted spatial pattern, temporal profile and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 264 publications
(422 reference statements)
1
7
0
Order By: Relevance
“…These analyses and observations provide insights into the mechanism of fibre-shaper-based spatiotemporal control and entertain the choice of SI MMFs for a broadband high-peak-power tunable fiber source. Our observation, although unexpected, is consistent with the recent studies that show GRIN MMFs are not as sensitive to launching conditions or bending as SI MMFs 52 , 62 64 . Despite it being a drawback to applications that demand insensitivity to bending, the usually undesirable susceptibility to bending of SI MMFs, together with their power scalability, are essential for achieving effective spatiotemporal control of high-power pulse propagation in multimode fibers.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These analyses and observations provide insights into the mechanism of fibre-shaper-based spatiotemporal control and entertain the choice of SI MMFs for a broadband high-peak-power tunable fiber source. Our observation, although unexpected, is consistent with the recent studies that show GRIN MMFs are not as sensitive to launching conditions or bending as SI MMFs 52 , 62 64 . Despite it being a drawback to applications that demand insensitivity to bending, the usually undesirable susceptibility to bending of SI MMFs, together with their power scalability, are essential for achieving effective spatiotemporal control of high-power pulse propagation in multimode fibers.…”
Section: Resultssupporting
confidence: 93%
“…The significantly smaller exhibited by GRIN MMFs can be attributed to the more confined mode field which sees weaker local perturbation at the center region (Fig. 3c, d, h, i ) and hence higher resistance to mechanical deformation such as bending 61 64 . Moreover, the clustering nature of the propagation constants in GRIN MMFs makes the perturbation-induced mode coupling tend to occur between the nearly degenerate modes, commonly referred to as the degenerate-mode group 65 .…”
Section: Resultsmentioning
confidence: 99%
“…Besides, opto-thermoelectric speckle tweezers have been developed very recently where an optical speckle field was fed into a thermal speckle field through interaction with plasmonic substrates, thus converting the high-intensity speckle grains into the corresponding thermal speckle grains . In that continuation, Čižmár et al described the true potential of a MM fiber for imaging, trapping, spectroscopy, and many more by their series of research articles. , However, the STs described above have predominantly been employed in liquid medium and demonstrate trapping in two dimensions. In the case of photophoretic-based trapping of particles in air, only Shvedov et al demonstrated that a volume speckle field generated by a coherent laser beam and diffuser can be used to confine a massive number of carbon particles in air using the photophoretic force , without investigating the trapping of single particles and the corresponding trap stiffness measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have developed novel techniques that utilize the deterministic nature of the multimode ber transmission matrix (TM) to perform bioimaging [30][31][32][33][34][35][36][37][38][39][40] . These approaches have enabled the acquisition of diffraction-limited images of uorescently labeled brain structures and neuronal activity, even in deep brain regions (e.g., head-xed mouse), using a multimode ber microendoscope 31 .…”
Section: Introductionmentioning
confidence: 99%
“…These approaches have enabled the acquisition of diffraction-limited images of uorescently labeled brain structures and neuronal activity, even in deep brain regions (e.g., head-xed mouse), using a multimode ber microendoscope 31 . To achieve this, however, an extensive characterization of MMFs transmission properties is necessary, ideally taking into account TM changes whenever the MMF ber is bending or changing its transmission properties during an experiment, as well discussed in previous research 32,40,41 . Consequently, while these techniques provide a minimally invasive method to obtain diffraction-limited resolution in deep brain regions, they are complex to implement and require a wavefront shaping device (e.g., spatial light modulator, SLM) to compensate for the uorescence randomized wavefronts through a lengthy calibration procedure.…”
Section: Introductionmentioning
confidence: 99%